Penggunaan Media Animasi Dalam Model Pembelajaran Langsung untuk Meningkatkan Hasil Belajar IPS Geografi Materi Interaksi Keruangan Dalam Kehidupan Negara – Negara Asean Kelas VIII SMP Negeri 70 Halmahera Selatan - Suaema, Andi; Halek, Dahri Hi; Bongso, Ikram (Jurnal Ilmiah Wahana Pendidikan, 2023)
The aim to be achieved in this research is to determine the results of students' geography social studies learning on Spatial Interaction in the Life of ASEAN Countries which is taught using animation media in a direct learning model. The research method used is quantitative and a type of Classroom Action Research (PTK). In this research, the research subjects were 27 students in class VII of SMP Negeri 70 South Halmahera, consisting of 14 male students and 13 female students. The results showed that the average pre-cycle learning outcome was 71.04 with classical completeness of 38.09%, in the first cycle the average was 72.33 with classical completeness of 60% and in the second cycle the average was 74 with classical completeness of 85.71. %. From these results it can be concluded that the implementation of this learning model was successful and provided an improvement in the learning outcomes of class VIII students at SMP Negeri 70 South Halamahera.